Adsorption mechanism of ZnO and CuO nanoparticles on two typical sludge EPS: Effect of nanoparticle diameter and fractional EPS polarity on binding. (January 2019) - Wei, Liangliang; Ding, Jing; Xue, Mao; Qin, Kena; Wang, Sheng; Xin, Ming; Jiang, Junqiu; Zhao, Qingliang
Abstract: Worldwide application of nanotechnology has led to an increasingly release of nanoparticles in wastewater treatment systems, and thus into sewage sludge, which potentially impairs the disposal of sewage sludge. Here, the binding process, adsorption characteristics, and the contribution of fractional polarity of extracellular polymeric substances (EPS) of anaerobic granular sludge (AGS) and activated sludge (AS) to the nano-ZnO and nano-CuO adsorption were investigated. Briefly, CuO-NPs can be more efficiently adsorbed by the EPS-AGS than that of ZnO-NPs (1.31 ± 0.08 g/g VS vs 0.53 ± 0.04 g/g VS), and a smaller diameter of nanoparticles benefited the adsorption processes. Hydrophobic EPS (HPO-A and HPO-N) within these two sludge were more effective in removing nano-CuO and ZnO than were the hydrophilic fraction. For example, HPO-A and HPO-N obtained from AGS showed a relatively higher adsorption abilities (in g/g VS) of 2.09 ± 0.12 and 2.27 ± 0.14, respectively, for nano-CuO, much higher than HPI (0.76 ± 0.04 g/g VS). Structural variations of the EPS before and after nanoparticles sorption were evaluated via the analysis of infrared spectroscopy, which showed that the functional structures of hydroxyl, amino, carboxyl, amide groups and C-O-C groups played a major role in nanoparticles binding/removal. Sorption process of nano-CuO and nano-ZnO on unfractionated EPS well fitted by Langmuir isotherm, as well as a pseudo second-order kinetic model. However, adsorption process of HPO-A can be better simulated by Freundlich equation. Graphical abstract: Image 1 Highlights: Nano-CuO could be more easily adsorbed by two sludge EPS than nano-ZnO. Hydrophobic EPS of sludge EPS adsorbed more nano-ZnO and nano-CuO than HPI. Smaller diameters of nanoparticles benefited their adsorption onto sludge EPS. Langmuir model fitted to unfractionated EPS adsorption while Freundlich for HPO-A.